Comparison of Hematocrit Values Using the Microhematocrit Method and the Automatic Hematology Analyzer - Suparyati; Maharani Putri, Delia (INDOGENIUS, 2025)
Background & Objective: Hematocrit is the percentage of erythrocyte volume in blood that is important for assessing health status, especially in relation to oxygen transport capacity. Hematocrit tests can be performed manually (microhematocrit) or automatically (hematology analyzer). Differences in the working principles of the two methods can cause variations in results. This study aims to determine the difference in hematocrit values using the microhematocrit method and the automatic hematology analyzer. Method: This study is analytical in nature with a quantitative approach, using 30 venous blood samples from outpatients at Kraton Pekalongan Regional General Hospital. The examination was performed using the microhematocrit method and the automatic hematology analyzer. The data were analyzed using normality tests and Paired Sample T-Tests using SPSS. Result: The average hematocrit value using the manual microhematocrit method was 33.33%, while the average value using the automatic hematology analyzer was 32.41%. The statistical test results showed a significant value of 0.075 (P> 0.05), indicating that there was no significant difference between the two methods. Conclusion: There was no significant difference between the hematocrit values obtained by the microhematocrit method and the automatic hematology analyzer. Both methods can be used interchangeably depending on the availability of equipment and clinical needs.